The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.psyneuen.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Thalamic neuropeptide mediating the effects of nursing on lactation and maternal motivation

Abstract: SUMMARY Nursing has important physiological and psychological consequences on mothers during the postpartum period. Tuberoinfundibular peptide of 39 residues (TIP39) may contribute to its effects on prolactin release and maternal motivation. Since TIP39-containing fibers and the receptor for TIP39, the parathyroid hormone 2 receptor (PTH2 receptor) are abundant in the arcuate nucleus and the medial preoptic area, we antagonized TIP39 action locally to reveal its actions. Mediobasal hypothalamic injection of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 50 publications
3
77
0
Order By: Relevance
“…Recent studies have identified a role for a 39 residue tuberoinfundibular peptide (TIP39) in the rat that binds to the parathyroid 2 receptor in both the MPOA and arcuate region in regulating suckling-induced prolactin secretion (Cservenák et al, 2010) and more recently maternal motivation (Cservenák et al, 2013). Retrograde studies by these investigators have identified that TIP39 producing cells that project to the arcuate region and medial preoptic area are located in the posterior intralaminar complex of the thalamus.…”
Section: Biochemical Regulation Of Maternal Behaviormentioning
confidence: 99%
“…Recent studies have identified a role for a 39 residue tuberoinfundibular peptide (TIP39) in the rat that binds to the parathyroid 2 receptor in both the MPOA and arcuate region in regulating suckling-induced prolactin secretion (Cservenák et al, 2010) and more recently maternal motivation (Cservenák et al, 2013). Retrograde studies by these investigators have identified that TIP39 producing cells that project to the arcuate region and medial preoptic area are located in the posterior intralaminar complex of the thalamus.…”
Section: Biochemical Regulation Of Maternal Behaviormentioning
confidence: 99%
“…These regions comprise several nodes of the sociosexual brain: the LSV, the MePD, BSTMPM, AC/ADP, MPO, VMHvl and adjoining tuberal region (hypothalamic aggression locus), and VLPAG (Newman 1999). We also included the magnocellular neurosecretory nuclei (Pa and SO) and other sites that are also involved in the regulation of maternal behaviours (CeM, AVPe, and PIL; Bosch and Neumann 2010;Scott et al 2015) or related aspects of motherhood (Cservenák et al 2013), despite not being usually considered as part of the sociosexual brain network. Finally, we also analysed the Arc, given its role in the feedback control of hypophyseal PRL release (Ben-Jonathan and Hnasko 2001; Sapsford et al 2012).…”
Section: Quantitative Analysis Of Pstat5-ir In the Brain Of Virgin Pmentioning
confidence: 99%
“…4f). This region is known to be a relay station for ascending somatosensory information of the ventral region of the body, which allows suckling stimulation to trigger the release of PRL during lactation (Cservenák et al 2013). Therefore, it is tempting to suggest a role of pSTAT5-ir in this region in feedback regulation of suckling-induced PRL release through a central modulation of sensitivity to suckling stimulation.…”
Section: Prolactin Signalling In the Brain Of Virgin Female Micementioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that TIP39-expressing neurons regulate prolactin release via their projections to the arcuate nucleus (Cservenak et al 2010; Dobolyi et al 2010). TIP39, a neuropeptide originally purified from the hypothalamus (Usdin et al 1999), may also contribute to the control of maternal motivation (Cservenak et al 2013). Therefore, we examined the possible connection between TIP39 and preoptic galanin neurons by comparing their topographical distributions.…”
Section: Introductionmentioning
confidence: 99%